El turismo y su impacto en el desarrollo del municipio de Tacámbaro, Michoacán, México, 2024 - Jaramillo Ayala, María Esperanza (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Since 2012, Tacámbaro municipality, in Michoacán, Mexico joined to Federal Magical Towns Program and promote tourism activity were initiated. In 2019, federal financing of Magic Towns Program was canceled. It changed municipal development direction and break promote tourism activity program continuity. Also, uncertainty awakened in local investors regarding possibilities for endogenous development reduction in Tacámbaro municipality. Tourism activity impacts in a positive and significant way on the economic, social, cultural and environmental development of the municipality of Tacámbaro was the hypothesis proposed. The objectives of this work were to determine if tourism influences the economic, social, cultural and environmental development, and to analyze how it impacts local development. Surveys were designed and applied to obtain direct information from visitors, local population, and the public and private sectors of Tacámbaro. Data analysis of resultant information was performed using Cronbach's Alpha and PLS-SEM to evaluate and understand subsequent models. The PLS-SEM models validated the proposed hypothesis with two of the three prediction values. Tourist activity municipal development project based must be sustainable over time, and must integrate cultural, natural and socioeconomic aspects of tacambarense people. Integral benefits and standard of living improvement for local population will occur from jobs generation, economic activities and concrete actions focused on investment of resources. Alternative, non-massive tourism proposals aimed at the appreciation of cultural and natural heritage of Tacámbaro.

Desde 2012 el municipio de Tacámbaro, en Michoacán, México se adhirió al Programa Federal Pueblos Mágicos y se inició la actividad turística de promoción. En 2019 se canceló el financiamiento federal del Programa Pueblos Mágicos. Cambió rumbo de desarrollo municipal y se rompió el impulso a la continuidad del programa de promoción a la actividad turística. También despertó la incertidumbre en los inversionistas locales respecto a las posibilidades de reducción del desarrollo endógeno en Tacámbaro. La actividad turística impacta de una manera positiva y significativa en el desarrollo económico, social, cultural y ambiental del municipio de Tacámbaro fue la hipótesis planteada. Los objetivos de este trabajo son determinar si el turismo influye en el desarrollo económico, social, cultural y ambiental y analizar de qué manera impacta en el desarrollo local. Se diseñaron y aplicaron encuestas destinadas a obtener información directa de los visitantes, población local, y los sectores público y privado de Tacámbaro. El análisis de datos de la información resultante se realizó mediante el Alfa de Cronbach y PLS-SEM para evaluar e interpretar los modelos consecuentes. Los modelos PLS-SEM validaron la hipótesis planteada con valores de predicción. La actividad turística basada en un proyecto de desarrollo municipal debe ser sostenible en el tiempo, y debe integrar los aspectos culturales, naturales y socioeconómicos del pueblo tacambarense. Los beneficios integrales y la mejora del nivel de vida de la población local se producirán a partir de la generación de empleos, actividades económicas y acciones concretas centradas en la inversión de recursos: Propuestas de turismo alternativo, no masivo, orientadas a la valorización del patrimonio cultural y natural de Tacámbaro.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: info:eu-repo/classification/cti/5; ININEE-D-2025-0573; Turismo; Economía; Desarrollo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19198